Incidencia de la atención motivada en el proceso de aprendizaje de los niños de primer año de educación básica de la Escuela Fiscal Zoila Ugarte de Landivar, del cantón El Guabo, en el período lectivo 2011-2012. - Ajila Sárez, Jessica Karina (2012)
This research makes us think that at present, the company has formed a misconception of what is to educate, because they think it is a task that falls exclusively to a particular school, so being that both parents and the society are evading their responsibilities in this process.